GC clusters and the stability of mitochondrial genomes of Saccharomyces cerevisiae and related yeats - Spírek, M; Soltésová, A; Horváth, A; Sláviková, E; Sulo, P (Folia microbiologica, 2002)
The occurrence of GC clusters in Saccharomyces spp. and related yeasts was examined to clarify their association with the stability of intact mitochondrial genome. Abundance of nonspecific or specific GC clusters in these species decreases with phylogenetic distance from S. cerevisiae. Their number but not the number of replication origins correlates with the ability to form respiration-deficient mutants induced by ethidium bromide. This effect is not associated with the nuclear background since the cybrids having identical nuclei and mitochondria from different species gave similar results. In contrast to grand genomes, the presence of GC clusters in rho- mutants does not play any role in ethidium bromide induced mtDNA loss. The most plausible explanation for mitotically lost petite mtDNA seems to be dilution during the distribution.
Keywords: genotyp; GC Rich Sequence; DNA, Fungal; DNA fungální; Base Composition; zastoupení bazí; Restriction Mapping; Ethidium; GC bohatá sekvence; restrikční mapování; mutace; Genotype; Mutation; ethidium; mitochondriální DNA; DNA, Mitochondrial; Saccharomyces cerevisiae